Management of wastes through public-private partnerships for composting in developing economies - Exell, Kristina Gabrielle Alexis (Universidad ESAN, 2017)
The objective of this thesis is to explore how a solid waste management programme for composting and the sale of compost, as distinct from other waste disposal activities, would be enabled by the Public-Private Partnership (PPP) model. More specifically, the goals of this thesis are to identify and analyze the factors that would make a composting PPP effective, based on the international experience; to identify the key actors and incentives that operate for the composting PPP contract; and thirdly, to assess the relevance of the identified factors, actors and incentives as may be applied to a selected developing economy, namely Jamaica. In order to achieve the objectives, the following questions are answered: i. Based on the international experience, what are the factors necessary to make a composting PPP effective? ii. Which are the key actors and incentives that operate for the composting PPP contract? iii. How may the identified factors, actors and incentives be relevant as applied to the case of a developing economy, namely Jamaica?
Keywords: Administración de desperdicios; Sector público; Sector privado; Abonos y fertilizantes; https://purl.org/pe-repo/ocde/ford#5.02.04